DAMPAK EPILEPSI PADA KEHAMILAN - Andi Muhammad Al Fatih Haq (Jurnal Medika Hutama, 2025)
Epilepsy is one of the most common chronic neurological conditions. It can affect individuals of all age groups, including women of reproductive age. In the United States, more than one million women of reproductive age are living with epilepsy. Epilepsy in this group, especially in pregnant women, requires special attention due to its potential impact on both the mother and fetus. In addition to the risk of external trauma from falls or injuries during seizures, seizures during pregnancy can also cause other negative outcomes, such as fetal distress, intrauterine growth restriction (IUGR), spontaneous abortion, preeclampsia, preterm birth, and even a tenfold increase in maternal mortality risk. Additionally, some antiepileptic drugs, such as valproic acid, can have teratogenic effects. Although the majority (90%) of pregnant women with epilepsy can deliver safely and have favorable pregnancy and birth outcomes, women with epilepsy still face a higher risk of adverse pregnancy outcomes. Therefore, understanding the impact of epilepsy during pregnancy and how to recognize and mitigate these risks is essential.